2020
DOI: 10.3390/jcm9061619
|View full text |Cite
|
Sign up to set email alerts
|

A Translational In Vivo and In Vitro Metabolomic Study Reveals Altered Metabolic Pathways in Red Blood Cells of Type 2 Diabetes

Abstract: Clinical parameters used in type 2 diabetes mellitus (T2D) diagnosis and monitoring such as glycosylated haemoglobin (HbA1c) are often unable to capture important information related to diabetic control and chronic complications. In order to search for additional biomarkers, we performed a pilot study comparing T2D patients with healthy controls matched by age, gender, and weight. By using 1H-nuclear magnetic resonance (NMR) based metabolomics profiling of red blood cells (RBCs), we found that the metabolic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 88 publications
(89 reference statements)
5
26
0
Order By: Relevance
“…Recent evidence has suggested that T2DM individuals display altered creatine metabolism [26,27]. In a prospective cohort study including more than 4700 participants, Post et al [27] observed that higher plasma creatine concentration was associated with increased incidence of T2DM.…”
Section: Insulin Resistance In the Context Of The Interplay Between Cmentioning
confidence: 99%
“…Recent evidence has suggested that T2DM individuals display altered creatine metabolism [26,27]. In a prospective cohort study including more than 4700 participants, Post et al [27] observed that higher plasma creatine concentration was associated with increased incidence of T2DM.…”
Section: Insulin Resistance In the Context Of The Interplay Between Cmentioning
confidence: 99%
“…Additionally, plasma creatine itself was strongly associated with an increased risk of incident type 2 diabetes in males, but not in females. In a recent metabolomic study of human erythrocytes, it was shown that the creatine content of erythrocytes in patients with type 2 diabetes was also higher than that of healthy controls 57 . Unfortunately, no sex‐stratified analyses were performed in this study.…”
Section: Discussionmentioning
confidence: 86%
“…They only conserve a few metabolic pathways for obtaining energy and reduce the energy consumption for the key functions they need to fulfil. This makes erythrocytes highly sensitive to any disorder [ 77 ]. Glucose metabolism disorders in patients with diabetes profoundly affect the morphological structure and physiological functions of erythrocytes ( Figure 2 ) and result in insufficient microcirculation perfusion, hypoxia, and OS, which promoting the occurrence of diabetic complications and reducing the quality of life of diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…They only conserve a few metabolic pathways for obtaining energy and reduce the energy consumption for the key functions they need to fulfil. This makes erythrocytes highly sensitive to any disorder [77]. Glucose…”
Section: Discussionmentioning
confidence: 99%